2014
DOI: 10.1007/s10566-014-9250-5
|View full text |Cite
|
Sign up to set email alerts
|

Personal and Contextual Factors Related to Internalizing Problems During Adolescence

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 61 publications
2
24
1
2
Order By: Relevance
“…() and Oliva et al . (). They found that high psychological, low autonomy support and self‐esteem were all associated with adolescents’ internalizing problems after controlling age and socioeconomic status.…”
Section: Discussionmentioning
confidence: 97%
“…() and Oliva et al . (). They found that high psychological, low autonomy support and self‐esteem were all associated with adolescents’ internalizing problems after controlling age and socioeconomic status.…”
Section: Discussionmentioning
confidence: 97%
“…Internalizing symptoms appear to be endorsed more strongly by girls than by boys (Hankin and Abramson 2001;Oliva et al 2014;van Oort et al 2009). Specifically, during adolescence, females are at peak risk for onset of depression: girls are two to three times more likely than boys to report depression, a gender difference that persists throughout the life span (Hankin et al 1998).…”
Section: Gender-related Effects and Ethnic Differencesmentioning
confidence: 91%
“…Indeed, risk factors for internalizing problems occur at multiple levels and contexts, including adolescent-specific factors (e.g., genetics, temperament, and negative emotionality), insecure parent attachment (e.g., Groh et al 2012;Madigan et al 2013), parenting practices (e.g., parental rejection or overcontrol), parents' psychopathology, stressful life events (e.g., Pine et al 2002;Sheeber et al 2001Sheeber et al , 2007 and macro-level contexts such as culture and socioeconomic opportunities. In addition to considering multiple influences on internalizing symptoms, it will be also important to consider factors that may moderate and/or mediate the relation of peer attachment quality with internalizing problems (*Kullik and Petermann 2013; Oliva et al 2014). …”
Section: Suggestions For Future Researchmentioning
confidence: 99%
“…Although, the role of fathers has been less frequently explored, some authors have reported an adverse impact of the father commenting on their daughters' body shape and weight and eating behaviors (Keery, Boutelle, van den Berg, & Thompson, 2005), or on their sons' muscularity (McCreary, 2012). Alongside parents, peers become of high relevance for the psychological functioning and overall behavior during adolescence (Oliva, Parra, & Reina, 2014;Story et al, 2002). Alongside parents, peers become of high relevance for the psychological functioning and overall behavior during adolescence (Oliva, Parra, & Reina, 2014;Story et al, 2002).…”
Section: Introductionmentioning
confidence: 99%